The Bioarchaeology of Disability in Medieval Times: An Overview of Current Perspectives and Future Directions - Matczak, Magdalena (Archaeologia Historica Polona, 2025)
Since the 1970s, archaeological research into disability has evolved into a distinct and mature field, known as the bioarchaeology of disability, characterized by specialized methodologies and theoretical approaches. Particularly, research on disability within medieval bioarchaeology has developed more extensively than in other periods of time. This article aims to offer a comprehensive and critical review of the literature on the bioarchaeology of disability, focusing on the Middle Ages. It examines the range of topics, methodologies, theories, and definitions of disability, as well as the methods used to investigate disability. Key research themes include various aspects of daily life, such as care, diet, prosthetics use, punishment, emotional experiences, and burial practices. The theoretical framework of the bioarchaeology of care has become dominant, leading to a focus on how disabled individuals were treated during the Middle Ages, with an emphasis on studies that highlight care. Osteobiography is another significant approach, often used in conjunction with the bioarchaeology of care. Social and multifactorial models are commonly employed to define disability. The field has advanced significantly through the application of new methods and techniques from medicine and biogeochemistry. Future research is expected to broaden the scope of topics, include population-level studies, and comparative analyses across Europe. Another challenge is to better integrate osteological analysis with historical texts to clarify which diseases and conditions were considered disabilities in the Middle Ages. A table providing examples of disability cases from the medieval period is included for reference.